Posterior Knee Pain: An Unusual Cause - Samdany, Alamgir; Ahmed, Guljar; Ahsan, Abdul Gani (Journal of Enam Medical College, 2015)
The pain around the posterior knee called popliteal fossa has been known to be caused by a variety of disease entities. Whatever the causes, the challenge remains in diagnosis. Proper history and clinical examination followed by uses of appropriate diagnostic tools are secrets to success. Venous malformation is a very rare cause of pain in popliteal area and its diagnosis is frequently delayed, missed or given incorrectly. Here, we report a case of a 24-year-old patient who presented with posterior knee pain for 2 years and was diagnosed as a case of intramuscular arterio-venous malformation by lower limb angiography. This patient was treated successfully by surgical resection. His follow-up was satisfactory with no evidence of recurrence. DOI: http://dx.doi.org/10.3329/jemc.v5i1.21499 J Enam Med Col 2015; 5(1): 58-60